2009
DOI: 10.1080/14992020902998409
|View full text |Cite
|
Sign up to set email alerts
|

The effect of hearing impairment in older people on the spouse: Development and psychometric testing of The Significant Other Scale for Hearing Disability (SOS-HEAR)

Abstract: The effects of hearing impairment on the person with the impairment and on their significant others are pervasive and affect the quality of life for all involved. The effect of hearing impairment on significant others is known as a third-party disability. This study aimed to develop and psychometrically test a scale to measure the third-party disability experienced by spouses of older people with hearing impairment. The Significant Other Scale for Hearing Disability (SOS-HEAR) was based on results of a previou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
69
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(72 citation statements)
references
References 24 publications
(44 reference statements)
0
69
0
Order By: Relevance
“…There is a small but growing body of research into the impact of hearing diffi culties on the family members and core conversational partners of people with hearing impairment (Armero, 2001;Brooks et al, 2001;Hallberg & Barren ä s, 1993;Hallberg, 1999;H é tu et al, 1993, 1988Jones et al, 1987;Scarinci et al, 2008Scarinci et al, , 2009aScarinci et al, , 2009bStark & Hickson, 2004;Wallhagen et al, 2004). This body of research has found that family members can experience considerable communication diffi culties, psychosocial stresses, reduced intimacy in the relationship with the person with hearing impairment, and decreased quality of life.…”
mentioning
confidence: 95%
“…There is a small but growing body of research into the impact of hearing diffi culties on the family members and core conversational partners of people with hearing impairment (Armero, 2001;Brooks et al, 2001;Hallberg & Barren ä s, 1993;Hallberg, 1999;H é tu et al, 1993, 1988Jones et al, 1987;Scarinci et al, 2008Scarinci et al, , 2009aScarinci et al, , 2009bStark & Hickson, 2004;Wallhagen et al, 2004). This body of research has found that family members can experience considerable communication diffi culties, psychosocial stresses, reduced intimacy in the relationship with the person with hearing impairment, and decreased quality of life.…”
mentioning
confidence: 95%
“…In the present study, the hearing disability perceived by others and self Intervention Questionnaire component-consisting of three items focusing on others' perception of the hearing disability and one item on self-perception of hearing disability (see Table 1)-was associated with intervention decisions, whereas scores on the HHQ were not. This suggests that a hearing disability's impact on others (Scarinci, Worrall, & Hickson, 2009) is central to intervention decisions for adults with acquired hearing impairment. The literature is unequivocal on the positive relationship between selfreported hearing disability and hearing help seeking and hearing aid uptake (e.g., Davis, Smith, Ferguson, Stephens, & Gianopoulos, 2007;Duijvestijn et al, 2003;Humes, Wilson, & Humes, 2003;Meister, Walger, Brehmer, von Wedel, & von Wedel, 2008;Stephens, Meredith, Callaghan, Hogan, & Rayment, 1990;Swan & Gatehouse, 1990;van den Brink et al, 1996).…”
Section: Hearing Disability Perceived By Others and Selfmentioning
confidence: 99%
“…In a series of studies, Scarinci, Worrall, and Hickson (2008, 2009a, 2009b demonstrated that older spouses experience third-party hearing disability as a result of their partners' hearing impairment. A literature review documented the lack of research on problems faced by significant others of older people with hearing impairment, providing a rationale for further investigation (Donaldson, Worrall, & Hickson, 2004).…”
Section: Summary Of Third-party Hearing Disability Researchmentioning
confidence: 99%
“…Further investigation is needed to establish the reliability of the instrument (Scarinci et al, 2009a).…”
Section: Summary Of Third-party Hearing Disability Researchmentioning
confidence: 99%